Harnessing endophytic microorganisms for sustainable plant virus management: Mechanisms, applications and prospects - Siva, R S; Kannan, R; Gopalakrishnan, C; Preetha, G; Swarnakumari, N; Jayakanthan, M (Plant Science Today, 2026)
Plant viruses represent a persistent and severe threat to global crop productivity with conventional management strategies often proving inadequate. This review highlights the emerging potential of endophytic microorganisms as a sustainable approach to plant virus management. We synthesize current advances on the diverse mechanisms through which bacterial and fungal endophytes exert antiviral effects, including the induction of systemic resistance, production of antiviral metabolites and direct competition with pathogens. Translational applications from screening and formulation to field deployment are examined to underscore their potential as novel biocontrol agents. Despite encouraging progress, challenges such as variability in efficacy, ecological adaptability and commercialization barriers remain. We critically evaluate these limitations and discuss future perspectives, emphasizing the integration of advanced omics technologies and synthetic biology to design next-generation microbial inoculants.